2013
DOI: 10.1002/jgrd.50599
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol particles at a high‐altitude site on the Southeast Tibetan Plateau, China: Implications for pollution transport from South Asia

Abstract: at Lulang, a high-altitude (>3300m above sea level) site on the southeast Tibetan Plateau (TP); objectives were to determine chemical characteristics of the aerosol and identify its major sources. We report aerosol (total suspended particulate, TSP) mass levels and the concentrations of selected elements, carbonaceous species, and water-soluble inorganic ions. Significant buildup of aerosol mass and chemical species (organic carbon, element carbon, nitrate, and sulfate) occurred during the premonsoon, while lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 65 publications
8
107
1
Order By: Relevance
“…4). This supports the findings of other studies in Lijiang and the south TP (Zhang et al, 2011, Zhao et al, 2013.…”
Section: Elemental Compositionsupporting
confidence: 93%
See 2 more Smart Citations
“…4). This supports the findings of other studies in Lijiang and the south TP (Zhang et al, 2011, Zhao et al, 2013.…”
Section: Elemental Compositionsupporting
confidence: 93%
“…However, the greatest concentration of NO 3 -was observed during the pre-monsoon period and that of SO 4 2-and NH 4 + during the monsoon period, which indicates that there are additional sources of NO 3 -during the pre-monsoon period and SO 4 2-and NH 4 + during the monsoon period, respectively. Previous studies have shown that the largest total ionic concentration occurred during the pre-monsoon period at other sites along the south edge of the TP (Shrestha et al, 2000;Desesari et al, 2010;Zhao et al, 2013). However, our data shows that the largest total detected ionic concentration was observed during monsoon period, which was caused by the large concentrations of SO 4 2-and NH 4 + during this period (Table 2).…”
Section: Elemental Compositioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Pollutants may reach higher elevations or move farther to the inland TP through long-range transport (Ming et al, 2010;Xia et al, 2011;Zhao et al, 2013;Lüthi et al, 2015). In addition, air masses are transported from South Asia year-round (Fig.…”
Section: Potential Source Regionsmentioning
confidence: 99%
“…Most aerosol chemistry investigations in the TP were short-term and conducted at the edge of the plateau (e.g., Wen et al, 2001;Cong et al, 2007;Meng et al, 2013;Zhao et al, 2013) and Lhasa, the capital city of the Tibet Autonomous Region of China (Zhang et al, 2000;Cong et al, 2011). Therefore, considering the vast area of the TP and the very limited data available for the region, more investigations are required to understand the aerosol chemical composition over the TP, particularly in the remote and inland TP.…”
Section: Introductionmentioning
confidence: 99%